Biomechanical study of Seoi-nage in judo - influence of elbow's pain on motion - - Yamamoto, Y.; Fujii, N. (ISBS Proceedings Archive (Michigan), 2019)
The aim of this study is to clarify Seoi-nage technique for reducing injuries in elbow joints. Uchikomi and Nagekomi were used as the trials. Two judo athletes with pain in elbow and three athletes without pain in elbow were instructed to perform the Seoi-nage as Tori. Strain gauge sensors were set in a judo cloth to measure the force applied by Tsurite (hand grasping the Eri). The results were observed as the follows: i) The athletes without pain applied a large force towards the throwing direction by the internal-rotation of shoulder. ii)In athlete with pain, the force direction was not towards throwing direction, but towards the left rotating side. The group without pain had an ideal movement of applyingSeoi-nage. On the other hand, thegroup with pain did not apply kuzushi, but generate force to throw the Uke by putting flexing the trunk with external-rotation position of the shoulder.